Philosophy in the digital epoch: potential development and challenges - Mariya Chikarkova (Cхід, 2019)
The world of digital technologies is reformatting socio-humanitarian knowledge, in which digital humanities are actively developing, bringing together the hard sciences and humanities. It began to take shape form in the middle of the XXth century, and due to digital humanities, traditional philosophical questions received new perspectives also. The huge amount of digitized information does not simplify, but often complicates the search for true knowledge, pushing to epistemological pessimism. Blurring the boundaries between the physical world and the computer virtual environment in a new way raises the ontological question of reality itself and its boundaries. The ability to create a new person (s) in a virtual environment often causes not only psychological, but also axiological problems, contributes to the crime of ethical norms, and leads to alienation between people. In the field of philosophical anthropology, the gradual cyborgization of society modifies the question of the essence of man (Transhumanism, etc.). A new branch of philosophical knowledge, digital philosophy, is developing actively. It can be interpreted in two directions: simple digitization of philosophical texts and visualization of philosophy or an interdisciplinary field at the intersection of metaphysics and cosmology. All the above allows us to speak about the formation of new vectors of philosophical knowledge: media philosophy, digital philosophy, etc.